2018
DOI: 10.3390/molecules23030599
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking, and Antimycotic Evaluation of Some 3-Acyl Imidazo[1,2-a]pyrimidines

Abstract: A series of 3-benzoyl imidazo[1,2-a]pyrimidines, obtained from N-heteroarylformamidines in good yields, was tested in silico and in vitro for binding and inhibition of seven Candida species (Candida albicans (ATCC 10231), Candida dubliniensis (CD36), Candida glabrata (CBS138), Candida guilliermondii (ATCC 6260), Candida kefyr, Candida krusei (ATCC 6358) and Candida tropicalis (MYA-3404)). To predict binding mode and energy, each compound was docked in the active site of the lanosterol 14α-demethylase enzyme (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The most frequent positions for such interactions are 310, 312, 372, 462, 463 and 468 for His, 379 and 381 for Arg, and 143 for Lys. In this research, as well as in previous studies, we corroborated that the following amino acids: Tyr118, Phe145, Ile231, Met306, His310, Thr311, Ser378, Val509 and Val511 are involved in the active site of CYP51 of C. albicans [80,83,86].…”
Section: Generating 3d Models Of Cyp51 Enzymes Of Candida Sppsupporting
confidence: 89%
See 1 more Smart Citation
“…The most frequent positions for such interactions are 310, 312, 372, 462, 463 and 468 for His, 379 and 381 for Arg, and 143 for Lys. In this research, as well as in previous studies, we corroborated that the following amino acids: Tyr118, Phe145, Ile231, Met306, His310, Thr311, Ser378, Val509 and Val511 are involved in the active site of CYP51 of C. albicans [80,83,86].…”
Section: Generating 3d Models Of Cyp51 Enzymes Of Candida Sppsupporting
confidence: 89%
“…Ramachandran plots were also created for each model (Figures S69-S74), showing over 90% of the amino acid residues in the most favorable regions. Moreover, the models proved to be of good quality, as in previous studies by our group [80]. Docking simulations were carried out for the two series of 2-amino-3-cyano-4Hchromenes, 4a-o and 6a-h, at the active site of the CYP51 of Candida spp.…”
Section: Generating 3d Models Of Cyp51 Enzymes Of Candida Sppmentioning
confidence: 72%
“…From our study it is found that a higher binding affinity acts between the Ag/Sn-SnO 2 NPs and lanosterol 1 4a-demethylase (À7.71 kcal mol À1 ) (Table 1) as compared to the earlier reported results for the uconazole (À4.44 kcal mol À1 ) or ketoconazole (32.55 kcal mol À1 ). 74 Further from this study it is evident that the binding of Ag/Sn-SnO 2 is possible with the active heme interacting pocket. It can be noted that the Lys143 of lanosterol 1 4a-demethylase is involved in ionic interaction with the heme ring and it affects the beta bulge.…”
Section: Probable Mechanism Studymentioning
confidence: 57%
“…If the binding energy is less than 0, the compound (ligand) and protein (receptor) can bind spontaneously. If binding energy ≤ −1.2 kCal/mol, the ligand–receptor was considered stable ( Gomez-Garcia et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%